Postpartum feeding and resting behaviour of primiparous and pluriparous crossbred cows reared under loose housing - Patbandha, Tapas Kumar; Mohanty, Tushar Kumar; Tiwari, Siwani; Kumaresan, A; Bhakat, Mukesh; Baithalu, Rubina K; Sreela, Latika (Indian Journal of Dairy Science, 2018)
Present study was conducted to find out any alteration of feeding and resting behaviour of primiparous (n=11) and pluriparous (n=14) crossbred cows reared under loose housing system immediately following calving upto day 14 postpartum. Feeding and resting behaviour of cows were monitored in a fresh cow pen continuously using close circuit cameras. Stocking density in the pen was maintained 4-6 cows and provided with manger space of 6 meters and 66 m2 resting area. There was no significant difference of overall mean daily feeding time (291.64±15.07 and 279.48±11.37 min/day), number of feeding bout (14.81±0.71 and 12.92±0.77 numbers/day) and feeding bout duration (22.17±1.89 and 23.70±1.22 min/bout), respectively between primiparous and pluriparous cows (P>0.05) during 2 weeks postpartum. Similarly, overall mean daily lying time (527.90±11.24 vs. 549.39±6.86 min/day), number of lying bout (7.68±0.11 and 7.76±0.23 bouts/day) and lying bout duration (78.93±2.31 and 77.02±1.97 min/bout), respectively did not differ between primiparous and pluriparous cows (P>0.05) during 2 weeks postpartum. However, primiparous cows had significantly higher number of feeding bouts than pluriparous cows on day 7 and 10 postpartum (P£0.05). In primiparous cows, feeding bout duration was significantly shorter on day 2 and 7 postpartum than pluriparous cows (P£0.05). Primiparous cows had significantly less lying time and shorter lying bout on day 1 postpartum compared to pluriparous cows (P£0.05). Results of the present study indicated that feeding and resting behaviours of primiparous cows did not alter in loose housing system during postpartum period when reared with pluriparous cows in a small group with optimum feeding space and resting area.